Biossorção de íons cromo de solução aquosa sintética e efluente de curtume utilizando macrófitas aquáticas - Rocker, Cristiana (2015)
Effluent containing toxic metals present serious risks to the environment and to living beings due to their persistence in the environment bioacumulam on trophic chain. The biosorption method has been widely tested in the treatment of these effluents, by presenting itself as a low-cost alternative and effective. The objective of this work was to analyze the process of biosorption of Cr(III) from aqueous solutions and synthetic tanning effluent using inactive biomass of aquatic macrophytes Pistia stratiotes in natura (PN) and chemically modified (PM), Salvinia molesta in natura (SN) and chemically modified (SM). The characterization of the biomasses and biosorption experiments as a function of pH, time, concentration of ion Cr(III), and desorption temperature for the purpose of determining the maximum capability of biosorption. By means of the scanning electron microscopy images of biosorbents showed uneven surfaces and heterogeneous, and in the infrared spectroscopy indicated that the chemical modification with sodium hydroxide and citric acid removed soluble phenolics and increased the carboxyl groups involved in the biosorption process. Kinetic studies showed that the average time required for the system come into balance is from 240 minutes, and all the biosorbents tested were adjusted by the pseudo-segunda order model, the biosorbents also modified adjusted intraparticle diffusion model. The results of biosorption in function of the concentration of the ion Cr(III), indicated the maximum capacity of each biosorbent. Of biosorbents in natura, SN presented the highest capacity of biosorption, with 25.70 mg g-1, on the other hand, the biomass modified PM reached capacity with 58.16 mg g-1. The results were adjusted the Freundlich isotherm, and the Langmuir model presented good adjustment to the modified biosorbents. Using the thermodynamic studies, it was found that these are spontaneous and exothermic reactions, and the results of desorption were higher for PM. The tests using raw effluent from tannery and biological treatment pond, SN proved to be more advantageous for use in the treatment of raw sewage and biological treatment pond, for presenting the highest rate of removal of Cr(III). Whereas the biomass of aquatic macrophytes P. stratiotes and S. molesta are abundant in the environment, the use of the same as biosorbent is favourable for the treatment of effluents.